THE USE OF INTEGRATED LEARNING MODEL IN INDONESIAN LANGUAGE: AN ANALYTICAL STUDY OF THE EFFECTIVENESS OF LEARNING PROCESS IN THE MERDEKA CURRICULUM ERA - Syam, Christanto; Effendy, Chairil; Martono, Martono; Olendo, Yudhistira Oscar; Putra, Zakarias Aria Widyatama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
The usage of multiple learning approaches from the remains of the 2013 curriculum cannot be abandoned, especially in the period of Merdeka curriculum. This study builds teacher activities on integrated learning approaches, specifically in Indonesian language acquisition with short story writing material. The relevance of utilizing this model is considered as biased and not in line with the features of learning in the current period. The goal of this study is to demonstrate the efficacy of using an integrated learning in the Merdeka curriculum era. This research is revealed using a qualitative descriptive strategy. In the Merdeka curriculum age, the utilization of an integrated learning strategy for short story writing content is still relevant and aligned with student product objectives. Furthermore, the integrated learning model used by the instructor is effective and efficient, as indicated by the preparation for the organized learning evaluation and alignment with the learning objectives. It should be a source of worry and adaptation for other Indonesian language instructors who wish to continue working with integrated learning models that have the features of learning models in the Merdeka curriculum period.